Application of Teaching and Quiz Material Media Towards ICT Literacy and Student Learning Results - Permatasari, Gita Ayu; Sutikno, Sutikno; Nurbaiti, Upik (Universitas Nurul Huda, 2020)
The objectives of this research aims to identifying the impact of online learning and quiz that actually drive better results for ICT Literacyfor physics and student exam results. We are doing this observation with 40 students at SMK Ar-Rahman Watusalam with the sampling group method. We are using questionnaire to evalute the authentic situation of ICT Literacy and the exam results of students before we are using online learning and quiz. The that online learning and quiz make better results for ICT Literacy and student exam results, because the condition of students' physics test scores after the application of online interactive quizzes which reached KKM (Minimum completeness criteria), which reached 75 students out of 40 with a percentage of 65% of students.